2019
DOI: 10.1186/s40494-019-0276-8
|View full text |Cite
|
Sign up to set email alerts
|

A new bio-based organogel for the removal of wax coating from indoor bronze surfaces

Abstract: In this research, we propose an advanced system for the cleaning of wax-based coatings applied on indoor bronzes. To this aim we developed a new kind of eco-friendly gel based on PHB (poly-3-hydroxybutyrate) used as thickening agent, biodiesel (BD) and dimethyl carbonate (DMC). BD is a mixture of methyl esters obtained from palm oil, which acts as cleaning agent while DMC was added as additional solvent to partially solubilize PHB and forming a gelly phase. For the first time a PHB-based gel obtained by mixing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Additionally, two broad peaks were detected at 2 θ ≈ 18–25° and 35–45°, indicating the presence of amorphous content in the extracted wax. A comparison of diffractograms of WCCB with extracted wax suggests that the disappearance of the 004 peaks in extracted wax could be associated with the solubilizing effect of non‐polar solvent 75 . The absence of peaks at 310 and 311 in WCCB could be attributed to the effect of pyrolysis temperature.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, two broad peaks were detected at 2 θ ≈ 18–25° and 35–45°, indicating the presence of amorphous content in the extracted wax. A comparison of diffractograms of WCCB with extracted wax suggests that the disappearance of the 004 peaks in extracted wax could be associated with the solubilizing effect of non‐polar solvent 75 . The absence of peaks at 310 and 311 in WCCB could be attributed to the effect of pyrolysis temperature.…”
Section: Resultsmentioning
confidence: 98%
“…68 The XRD ison of diffractograms of WCCB with extracted wax suggests that the disappearance of the 004 peaks in extracted wax could be associated with the solubilizing effect of non-polar solvent. 75 The absence of peaks at 310 and 311 in WCCB could be attributed to the effect of pyrolysis temperature. The diffractogram of the extracted wax is similar to that of petroleum wax.…”
Section: X-ray Diffractionmentioning
confidence: 99%
“…Nowadays organogels as cleaning systems have been explored mostly on paintings and graphic documents, being multi-component artifacts and strongly sensitive to solvents [81][82][83]. On the contrary, in the literature rare is evidence of their application in the branch of metal conservation [84,85]. The main critical aspect of such implementation appears to be the rigidity of such systems.…”
Section: Organogels For Organic Coatings Removalmentioning
confidence: 99%
“…From the chemical point of view, biodiesel is a blend of alkyl esters and long-chain fatty acids [84]: this makes it an appropriate solvent for non-polar substances.…”
Section: Biodiesel and Derivativesmentioning
confidence: 99%
“…New studies in metals and paintings cleaning are also reported: Baij et al [21] contributed to a better understanding of the impact of different methods of solvent application on oil paintings and highlighted important differences between these methods; Moretti et al [22] aimed at developing an efficient methodology for in situ assessing painting surfaces after the laser cleaning using optical coherence tomography (OCT) and reflection FT-IR spectroscopy complemented with laser induced fluorescence (LIF) spectroscopic measurements; Yiming et al [23] developed a new kind of eco-friendly gel based on PHB (poly-3-hydroxybutyrate), biodiesel (BD) and dimethyl carbonate (DMC) for the cleaning of wax-based coatings applied on indoor bronzes.…”
mentioning
confidence: 99%